Influence of thermal aging on microhardness and microstructure of Sn-0.3Ag-0.7Cu-xIn lead-free solders - Kanlayasiri, Kannachai; Ariga, Tadashi (My University, 2010)
Sn-0.3Ag-0.7Cu is a low-silver lead-free solder, and provides a thinner brittle Ag3Sn intermetallic layer during soldering process. In this paper, effects of thermal aging on microhardness, and microstructure of Sn-0.3Ag-0.7Cu-xIn lead-free solders were investigated. Indium was added to lower the melting temperature, and varied from 0.0 to 3.0 wt%. The solders were thermally aged at 100 °C for 1, 10, 100, and 1000 h. Results showed that microhardness of the solders decreases as the aging time increases, and average grain size of the microstructure is larger with the increase of the aging time. It was also found that the higher In content in the solder provides the greater decreasing rate of its microhardness. © 2010 Elsevier B.V. All rights reserved.
Keywords: Mechanical properties; Metals and alloys; Microstructure